Innovation as a Tool for Generating Value in the IT Services Sector - Biancolino, César Augusto; Maccari, Emerson Antonio; Pereira, Maurício Fernandes (Review of Business Management, 2013)
Facing growing competitiveness, innovation management in companies providing IT services has taken on a strategic and tactical design, a fact that can generate competitive advantages and reduce risks. The goal of this research is to identify parameters that are applicable to innovation management in the services field of IT companies. For research strategies, we carried out a literature search referring to innovation concepts, followed by a documentary research concerning the studied company’s processes. For research technique applied to the strategies adopted, we performed a qualitative assessment based on a questionnaire using the social scale of attitudes amongst employees working in an IT company’s services field. For the study’s main theoretical structure, we analyzed the concepts of innovation based on classical texts, which add up to a panel on innovation as an increasingly important factor in the economic scenario, besides crucial issues referring to the operation and implementation of innovation within enterprises. The results point to different elements capable of delivering value to IT businesses through innovation management. We concluded that, even in companies that already have pre-existing processes for dealing with the topic "innovation", there may be room for creating a process applied to innovation management. Our contribution, in this way, was to create added knowledge concerning the theory associated with aspects of innovation and the economic sectors linked to the provision of IT services.